Sports Human Resource Development Strategy in Elementary School - Abdul Halim; Alberth Supriyanto Manurung; Oman Unju Subandi; Alfredo Do Carmo (STAI Hubbulwathan Duri, 2025)
Developing sports human resources in elementary schools is essential for nurturing athletic talent and strengthening physical education from an early age. This systematic literature review explores strategies to improve the skills and effectiveness of educators, coaches, and support staff in elementary school sports programs. The review focuses on studies published between 2014 and 2024, sourced from reputable databases such as Scopus and Google Scholar. Inclusion criteria prioritized peer-reviewed articles addressing human resource development in elementary school sports settings, specifically within regional and national contexts. A thematic analysis was conducted to synthesize findings across selected studies. Four key strategies emerged: (1) continuous professional development for teachers and coaches, (2) incorporation of innovative and age-appropriate sports curricula, (3) active community and parental engagement, and (4) integration of digital tools to support skill-building and performance tracking. The analysis also highlights persistent challenges, including limited funding, insufficient policy frameworks, and the lack of customized training models tailored to the developmental needs of young learners. Findings emphasize the necessity of collaborative efforts between schools, local governments, and sports organizations to address these challenges and optimize human resource utilization. This review offers practical recommendations for policymakers, educators, and community stakeholders aiming to strengthen sports education infrastructure and promote youth development at the foundational level.